Alterations in PACAP-38-like immunoreactivity in the plasma during ictal and interictal periods of migraine patients. (October 2013) - Tuka, Bernadett; Helyes, Zsuzsanna; Markovics, Adrienn; Bagoly, Teréz; Szolcsányi, János; Szabó, Nikoletta; Tóth, Eszter; Kincses, Zsigmond Tamás; Vécsei, László; Tajti, János
Background: Recent studies on migraineurs and our own animal experiments have revealed that pituitary adenylate cyclase-activating polypeptide-38 (PACAP-38) has an important role in activation of the trigeminovascular system. The aim of this study was to determine the PACAP-38-like immunoreactivity (LI) in the plasma of healthy subjects, and parallel with the calcitonin gene-related peptide (CGRP)-LI in migraine patients in the ictal and interictal periods. Methods: A total of 87 migraineurs and 40 healthy control volunteers were enrolled in the examination. Blood samples were collected from the cubital veins in both periods in 21 patients, and in either the ictal or the interictal period in the remaining 66 patients, and were analysed by radioimmunoassay. Results: A significantly lower PACAP-38-LI was measured in the interictal plasma of the migraineurs as compared with the healthy control group ( p  < 0.011). In contrast, elevated peptide levels were detected in the ictal period relative to the attack-free period in the 21 migraineurs ( p PACAP-38  < 0.001; p CGRP  < 0.035) and PACAP-38-LI in the overall population of migraineurs ( p  < 0.009). A negative correlation was observed between the interictal PACAP-38-LI and the disease duration. Conclusion: This is the first study that has provided evidence of a clear association between migraine phases (ictal and interictal) and plasma PACAP-38-LI alterations.